Compact extruded sheath power cable with copper core cross-linked polyethylene and processing technology
Patent Information
- Application Number
- CN202510755413.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-06-06
AI Technical Summary
1、专利文件US20100186988A1公开了电力电缆,但是上述文件中的电力电缆多采用单一镀层,存在导电性不足,电阻较高的技术问题;
1.本发明通过梯度镀层导体与五类绞合工艺的协同设计,显著提升导电性与结构稳定性,结合介电常数梯度分布的绝缘层及复合屏蔽结构,实现局部放电量的突破性抑制与电磁屏蔽效能优化,辅以纳米增强型护套及超声交联和液氮骤冷制造工艺,使电缆同时具备超高机械强度、极低孔隙率及卓越阻燃特性,综合性能远超常规电力电缆;
Smart Images

Figure CN120581258B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cross-linked polyethylene insulated power cable technology, specifically to a copper core cross-linked polyethylene dense extruded sheathed power cable and its processing technology. Background Technology
[0002] Power cables are cables used to transmit and distribute electrical energy. They are commonly used in urban underground power grids, power plant lead-out lines, internal power supply for industrial and mining enterprises, and underwater transmission lines across rivers and seas. Power cables are cable products used to transmit and distribute high-power electrical energy in the main lines of the power system, therefore, it is necessary to ensure that power cables have priority adaptability.
[0003] The defects of existing power cables are: 1. Patent document US20100186988A1 discloses power cables, but the power cables in the above document mostly use a single plating layer, which has technical problems such as insufficient conductivity and high resistance. 2. Patent document US5006670A discloses a power cable, but the power cable in the above document has technical problems such as high conductor DC resistance and low current carrying efficiency. 3. Patent document US20170330649A1 discloses a power cable, but the power cable in the above document has a simple shielding structure, resulting in insufficient electromagnetic shielding effectiveness. 4. Patent document CN101814335A discloses a cross-linked polyethylene insulated double-sheathed power cable, but the power cable in the above document has technical problems such as insufficient sheath tensile strength and high porosity. Summary of the Invention
[0004] The purpose of this invention is to provide a densely extruded sheathed power cable with a copper core and cross-linked polyethylene and a processing technology thereon, so as to solve the technical problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a copper core cross-linked polyethylene dense extruded sheathed power cable, comprising, from the inside out: a conductor layer, a semi-conductive water-resistant layer, a cross-linked polyethylene insulation layer, a composite shielding structure layer, and a dense sheath layer; Conductor layer: formed by multiple strands of tin-plated copper wires through five types of stranding structure, wherein the diameter of a single wire is 0.18mm to 0.22mm, the outer diameter tolerance of the conductor is within ±0.02mm, and the surface of the copper wire has a gradient plating structure, including a nickel layer of 0.5 to 0.8μm, a silver layer of 1.2 to 1.5μm and an organosilicon protective layer of 0.1 to 0.2μm from the inside out; Semiconductor resistive water layer: The conductor layer is wrapped with a longitudinal wrapping process with an overlap rate of 15% to 20%; Cross-linked polyethylene insulation layer: an inner shielding layer, an insulation layer, and an outer shielding layer formed simultaneously through a three-layer co-extrusion process, with an extrusion temperature of 150℃~165℃ and an extrusion pressure of 18MPa~22MPa; The composite shielding structure layer includes: Copper wire braided shielding layer: formed by loosely braiding tin-plated copper wire with a diameter of 0.12mm at a coverage rate of 85% to 90% and a braiding angle of 45° ± 5°; Semiconducting resistive water tape: wrapped around the outer surface of the copper wire braided shielding layer in a spiral wrapping manner; Dense sheath layer: Made of low-smoke, halogen-free, flame-retardant polyolefin material, with a cross-sectional porosity of no more than 0.3% and a density of no less than 0.95 g / cm³. 3 Tensile strength not less than 18 MPa, comprising, by weight: 60-75 parts of ethylene-vinyl acetate copolymer; 8-12 parts of nano-sized silica; 15-20 parts of magnesium hydroxide flame retardant; 1.5–2.5 parts of silane coupling agent; Antioxidant 0.5–1.2 parts; 3-5 parts of aminated multi-walled carbon nanotubes.
[0006] Preferably, the tin-plated copper wire of the conductor layer is annealed under nitrogen protection before stranding. The annealing temperature is 450℃~480℃, the stranding speed is 12m / min~14m / min, the elongation of the copper wire after annealing is ≥35%, and a protective gas containing 0.5~1.0 vol% rare earth lanthanum is introduced during the annealing process.
[0007] Preferably, a ceramicized silicone rubber filler layer is provided between the copper wire braided shielding layer and the semiconducting resistive water tape, the oxygen index of the filler layer being not less than 35%, comprising: 100 parts of methyl vinyl silicone rubber matrix; 40-50 parts of aluminum hydroxide flame retardant; 15-20 parts glass powder; Platinum catalyst 0.5–1.0 parts; 5-8 parts of shape memory polyurethane microspheres.
[0008] Preferably, the forming mold of the dense sheath layer has a conical flow channel structure and is equipped with a rotary extrusion device with a rotation speed of 80 rpm to 120 rpm.
[0009] Preferably, when the conductor layer adopts a five-type stranded structure, the number of copper wires in each strand is distributed in an arithmetic sequence with a tolerance of 6 to 8 wires, the number of copper wires in the outermost strand is 50 to 60, and the strand pitch ratio of adjacent strands varies from 1:1.28±0.05, and the stranding gap is filled with silicone grease lubricant containing nano-diamond particles.
[0010] Preferably, the substrate of the semiconducting resistive water layer is a polyester fiber reinforced composite material, comprising: Low-density polyethylene 45-55 wt% Carbon nanotube conductive filler 8–12 wt%; Water-absorbing and expanding resin particles 15-20 wt%; Polyester staple fiber 10-15 wt%; Graphene quantum dots: 0.5–1.2 wt%.
[0011] Preferably, the radial dielectric constant gradient distribution of the cross-linked polyethylene insulation layer satisfies the following: dielectric constant ε1 of the inner shielding layer = 2.35 ± 0.05, ε2 of the insulation layer = 2.25 ± 0.03, and ε3 of the outer shielding layer = 2.40 ± 0.05. Furthermore, the insulation layer contains dispersed sheet-like boron nitride nanofillers with a mass fraction of 0.8% to 1.5% and a diameter-to-thickness ratio > 150:1.
[0012] Preferably, the tin-plated copper wire of the copper wire braided shielding layer is coated with a nano-silver / graphene composite coating with a thickness of 80-120 nm, and titanium dioxide photocatalytic particles with a diameter of 20-50 nm are embedded in the coating.
[0013] Preferably, the aminated multi-walled carbon nanotubes in the dense sheath layer have a length distribution of 5-15 μm and an outer diameter of 8-12 nm, and are chemically bonded to the matrix material through a polyethylene compatibilizer grafted with maleic anhydride.
[0014] Preferably, the processing steps for this copper core cross-linked polyethylene dense extruded sheathed power cable are as follows: S1. Conductor pretreatment: The tin-plated copper wire is annealed under nitrogen protection containing rare earth elements at an annealing temperature of 450℃~480℃. After cooling to 80℃, it is stranded at a speed of 12m / min~14m / min, and nano-diamond lubricant is sprayed simultaneously during the stranding process. S2. Insulation layer processing: longitudinally wrap the semi-conductive resistive water layer and preheat to 110℃~120℃ for roll forming; The three-layer co-extrusion process is carried out through a CCV overhead cross-linking production line with an extrusion temperature of 150℃~165℃ and a vulcanizing tube temperature divided into three zones. Zone 1: 180℃±5℃; Zone 2: 210℃±5℃; Zone 3: 230℃±5℃. S3. Composite shielding processing: Braided copper wire shielding layer, with a coverage of 85% to 90% and a braiding angle of 45° ± 5°; Spiral-wound semiconducting resistive water tape, with a wrapping tension of 3N to 5N; S4, Irradiation crosslinking: Basic irradiation of 12Mrad to 15Mrad using an electron accelerator; S5. Secondary crosslinking with steam: 0.8MPa~1.2MPa saturated steam treatment for 4h~6h, with ultrasonic oscillation of 5~8kHz applied during the treatment; S6. Sheath Forming: The sheath is processed using a two-stage extruder with a die pressure of 25MPa~30MPa and a screw length-to-diameter ratio of 32:1. After extrusion, it is immediately subjected to liquid nitrogen quenching treatment with a cooling rate ≥50℃ / s.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention significantly improves conductivity and structural stability through the synergistic design of gradient plated conductors and Category 5 stranding technology. Combined with an insulation layer with gradient dielectric constant distribution and a composite shielding structure, it achieves breakthrough suppression of partial discharge and optimization of electromagnetic shielding effectiveness. With the addition of a nano-reinforced sheath and ultrasonic cross-linking and liquid nitrogen quenching manufacturing process, the cable simultaneously possesses ultra-high mechanical strength, extremely low porosity, and excellent flame retardant properties, with comprehensive performance far exceeding that of conventional power cables. 2. This invention achieves ultra-high stranding density while significantly reducing the DC resistance of the conductor through the synergistic effect of rare earth element annealing and nano-diamond lubricant filling, simultaneously improving current carrying efficiency and mechanical stability, and combining ultrasonic-assisted cross-linking process to ensure structural precision consistency. 3. This invention achieves breakthrough suppression of partial discharge and leapfrog improvement in high-frequency electromagnetic interference shielding effectiveness through radial dielectric constant gradient design and innovative insulating layer of sheet-like boron nitride filler, combined with the cascade shielding mechanism of ceramicized silicone rubber filler layer and nano silver / graphene composite coating, thus greatly enhancing the reliability of high-voltage environments. 4. This invention achieves a high tensile strength, extremely low porosity, and excellent flame retardant properties by combining the chemical bonding enhancement of aminated carbon nanotubes with the deep synergy of rotary extrusion process. The microstructure is further solidified by liquid nitrogen quenching technology, making its comprehensive performance far exceed that of conventional sheaths. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the power cable structure of the present invention.
[0017] In the diagram: 1. Conductor layer; 2. Semiconductor resisting water layer; 3. Cross-linked polyethylene insulation layer; 4. Dense sheath layer; 5. Copper wire braided shielding layer; 6. Semiconductor resisting water tape. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Example 1: Please refer to Figure 1 An embodiment of the present invention provides a copper core cross-linked polyethylene dense extruded sheathed power cable, which, from the inside out, comprises: a conductor layer 1, a semi-conductive water-resistant layer 2, a cross-linked polyethylene insulation layer 3, a composite shielding structure layer, and a dense sheath layer 4. Conductor layer 1: It is formed by multiple strands of tin-plated copper wires through a five-type stranding structure, wherein the diameter of a single wire is 0.20mm, the outer diameter tolerance of the conductor is within ±0.02mm, and the surface of the copper wire has a gradient plating structure, including a nickel layer of 0.6μm, a silver layer of 1.4μm and an organosilicon protective layer of 0.15μm from the inside out; Semiconductor resistive water layer 2: The conductor layer is wrapped with a longitudinal wrapping process with an overlap rate of 18%; Cross-linked polyethylene insulation layer 3: an inner shielding layer, an insulation layer, and an outer shielding layer formed simultaneously through a three-layer co-extrusion process, with an extrusion temperature of 160℃ and an extrusion pressure of 20MPa; The composite shielding structure layer includes: Copper wire braided shielding layer 5: formed by loosely braiding tin-plated copper wire with a diameter of 0.12mm at an 88% coverage rate and a braiding angle of 45°; Semiconductor resistive water tape 6: wrapped in a spiral manner on the outer surface of the copper wire braided shielding layer; Dense sheath layer 4: Made of low-smoke, halogen-free, flame-retardant polyolefin material, with a cross-sectional porosity of no more than 0.3% and a density of no less than 0.95 g / cm³. 3 Tensile strength not less than 18 MPa, comprising, by weight: 68 parts of ethylene-vinyl acetate copolymer; 10 parts of nano-sized silica; 17 parts of magnesium hydroxide flame retardant; 2 parts of silane coupling agent; Antioxidant 0.8 parts; Four portions of aminated multi-walled carbon nanotubes; The tin-plated copper wire of conductor layer 1 is annealed under nitrogen protection before stranding. The annealing temperature is 460℃ and the stranding speed is 13m / min. After annealing, the copper wire elongation is ≥35%, and a protective gas containing 0.8 vol% rare earth lanthanum is introduced during the annealing process. A ceramicized silicone rubber filler layer is provided between the copper wire braided shielding layer 5 and the semi-conductive resistive water tape 6. The oxygen index of the filler layer is not less than 35%, and it includes: 100 parts of methyl vinyl silicone rubber matrix; 45 parts of aluminum hydroxide flame retardant; 18 parts glass powder; 0.8 parts platinum catalyst; Seven portions of shape memory polyurethane microspheres; The molding die for the dense sheath layer 4 has a tapered flow channel structure and is equipped with a rotary extrusion device with a rotation speed of 100 rpm. When conductor layer 1 adopts a five-type stranded structure, the number of copper wires in each strand is distributed in an arithmetic sequence with a tolerance of 7 wires. The number of copper wires in the outermost strand is 55, and the strand pitch ratio of adjacent strands changes in a 1:1.28 increment. The strand gap is filled with silicone grease lubricant containing nanodiamond particles. The substrate of the semiconducting resistive water layer 2 is a polyester fiber reinforced composite material, including: 50wt% low-density polyethylene; 10 wt% carbon nanotube conductive filler; 17wt% water-absorbing and expanding resin particles; 12 wt% polyester staple fiber; Graphene quantum dots 0.9 wt%; The radial dielectric constant gradient distribution of the cross-linked polyethylene insulation layer 3 satisfies the following: dielectric constant ε1=2.35 for the inner shielding layer, ε2=2.25 for the insulation layer, and ε3=2.40 for the outer shielding layer. Furthermore, the insulation layer contains sheet-like boron nitride nanofiller with a mass fraction of 1.1% and a diameter-to-thickness ratio >150:1. The surface of the tin-plated copper wire of the copper wire braided shielding layer 5 is coated with a nano-silver / graphene composite coating with a thickness of 100nm, and titanium dioxide photocatalytic particles with a diameter of 35nm are embedded in the coating. The dense sheath layer 4 contains aminated multi-walled carbon nanotubes with a length distribution of 10 μm and an outer diameter of 10 nm, which are chemically bonded to the matrix material through a polyethylene compatibilizer grafted with maleic anhydride. The processing steps for this copper core cross-linked polyethylene dense extruded sheathed power cable are as follows: S1. Conductor pretreatment: The tin-plated copper wire is annealed under nitrogen protection containing rare earth elements at a temperature of 465℃. After cooling to 80℃, it is stranded at a speed of 13m / min, and nano-diamond lubricant is sprayed simultaneously during the stranding process. S2. Insulation layer processing: Longitudinal wrapping of semi-conductive resistive water layer 2 and preheating to 115℃ for roll forming; The three-layer co-extrusion process is carried out through a CCV overhead cross-linking production line with an extrusion temperature of 160℃ and a vulcanizing tube temperature divided into three zones. Zone 1: 180℃; Zone 2: 210℃; Zone 3: 230℃. S3, Composite shielding processing: Braided copper wire shielding layer 5, coverage rate 88%, braiding angle 45°; Spiral-wound semiconducting resistive water tape 6, wrapping tension 4N; S4, Irradiation crosslinking: Basic irradiation of 13Mrad using an electron accelerator; S5, Steam secondary crosslinking: 1MPa saturated steam treatment for 5h, with 6kHz ultrasonic oscillation applied during the treatment; S6. Sheath Forming: The sheath is processed using a two-stage extruder with a die pressure of 28MPa and a screw length-to-diameter ratio of 32:1. After extrusion, it is immediately subjected to liquid nitrogen quenching treatment with a cooling rate of ≥50℃ / s.
[0020] Example 2: Please refer to Figure 1 An embodiment of the present invention provides a copper core cross-linked polyethylene dense extruded sheathed power cable, which, from the inside out, comprises: a conductor layer 1, a semi-conductive water-resistant layer 2, a cross-linked polyethylene insulation layer 3, a composite shielding structure layer, and a dense sheath layer 4. Conductor layer 1: It is formed by multiple strands of tin-plated copper wires through five types of stranding structure, wherein the diameter of a single wire is 0.18mm, the outer diameter tolerance of the conductor is within ±0.02mm, and the surface of the copper wire has a gradient plating structure, including a nickel layer of 0.8μm, a silver layer of 1.2μm and an organosilicon protective layer of 0.2μm from the inside out; Semiconductor resistive water layer 2: The conductor layer is wrapped with a 15% overlap rate using a longitudinal wrapping process; Cross-linked polyethylene insulation layer 3: an inner shielding layer, an insulation layer, and an outer shielding layer formed simultaneously through a three-layer co-extrusion process, with an extrusion temperature of 165℃ and an extrusion pressure of 18MPa; The composite shielding structure layer includes: Copper wire braided shielding layer 5: formed by loosely braiding tin-plated copper wire with a diameter of 0.12mm at a coverage rate of 90% and a braiding angle of 40°; Semiconductor resistive water tape 6: wrapped in a spiral manner on the outer surface of the copper wire braided shielding layer; Dense sheath layer 4: Made of low-smoke, halogen-free, flame-retardant polyolefin material, with a cross-sectional porosity of no more than 0.3% and a density of no less than 0.95 g / cm³. 3 Tensile strength not less than 18 MPa, comprising, by weight: 75 parts of ethylene-vinyl acetate copolymer; 8 parts of nano-sized silica; 20 parts of magnesium hydroxide flame retardant; 1.5 parts of silane coupling agent; Antioxidant 1.2 parts; Three portions of aminated multi-walled carbon nanotubes; The tin-plated copper wire of conductor layer 1 is annealed under nitrogen protection before stranding. The annealing temperature is 480℃ and the stranding speed is 12m / min. After annealing, the copper wire elongation is ≥35%, and a protective gas containing 1.0 vol% rare earth lanthanum is introduced during the annealing process. A ceramicized silicone rubber filler layer is provided between the copper wire braided shielding layer 5 and the semi-conductive resistive water tape 6. The oxygen index of the filler layer is not less than 35%, and it includes: 100 parts of methyl vinyl silicone rubber matrix; 40 parts of aluminum hydroxide flame retardant; 20 parts glass powder; 0.5 parts platinum catalyst; Eight portions of shape memory polyurethane microspheres; The molding die for the dense sheath layer 4 has a tapered flow channel structure and is equipped with a rotary extrusion device with a rotation speed of 80 rpm. When conductor layer 1 adopts a five-type stranded structure, the number of copper wires in each strand is distributed in an arithmetic sequence with a tolerance of 8 wires. The number of copper wires in the outermost strand is 50, and the strand pitch ratio between adjacent strands changes in a 1:1.32 manner. Silicon grease lubricant containing nano-diamond particles is filled in the stranding gap. The substrate of the semiconducting resistive water layer 2 is a polyester fiber reinforced composite material, including: 45 wt% low-density polyethylene; 12wt% carbon nanotube conductive filler; 15wt% water-absorbing and expanding resin particles; 15 wt% polyester staple fiber; Graphene quantum dots 0.5 wt%; The radial dielectric constant gradient distribution of the cross-linked polyethylene insulation layer 3 satisfies the following: dielectric constant ε1=2.4 for the inner shielding layer, ε2=2.22 for the insulation layer, and ε3=2.45 for the outer shielding layer. Furthermore, the insulation layer contains dispersed sheet-like boron nitride nanofillers with a mass fraction of 0.8% and a diameter-to-thickness ratio >150:1. The surface of the tin-plated copper wire of the copper wire braided shielding layer 5 is coated with a nano-silver / graphene composite coating with a thickness of 120nm, and titanium dioxide photocatalytic particles with a diameter of 20nm are embedded in the coating. The dense sheath layer 4 contains aminated multi-walled carbon nanotubes with a length distribution of 15 μm and an outer diameter of 8 nm. These nanotubes are chemically bonded to the matrix material through a polyethylene compatibilizer grafted with maleic anhydride. The processing steps for this copper core cross-linked polyethylene dense extruded sheathed power cable are as follows: S1. Conductor pretreatment: The tin-plated copper wire is annealed under nitrogen protection containing rare earth elements at a temperature of 480°C. After cooling to 80°C, it is stranded at a speed of 12 m / min, and nano-diamond lubricant is sprayed simultaneously during the stranding process. S2. Insulation layer processing: Longitudinal wrapping of semi-conductive resistive water layer 2 and preheating to 120℃ for roll forming; The three-layer co-extrusion process is carried out through a CCV overhead cross-linking production line with an extrusion temperature of 165℃ and a vulcanizing tube temperature divided into three zones. Zone 1: 185℃; Zone 2: 205℃; Zone 3: 235℃. S3, Composite Shielding Processing: Braided copper wire shielding layer 5, coverage 90%, braiding angle 40°; Spiral-wound semiconducting resistive water tape 6, wrapping tension 3N; S4, Irradiation crosslinking: Basic irradiation of 15Mrad using an electron accelerator; S5, Steam secondary crosslinking: 1.2MPa saturated steam treatment for 4h, with ultrasonic oscillation of 8kHz applied during the treatment; S6. Sheath Forming: The sheath is processed using a two-stage extruder with a die pressure of 25MPa and a screw length-to-diameter ratio of 32:1. After extrusion, it is immediately subjected to liquid nitrogen quenching treatment with a cooling rate ≥50℃ / s.
[0021] Example 3: Please refer to Figure 1 An embodiment of the present invention provides a copper core cross-linked polyethylene dense extruded sheathed power cable, which, from the inside out, comprises: a conductor layer 1, a semi-conductive water-resistant layer 2, a cross-linked polyethylene insulation layer 3, a composite shielding structure layer, and a dense sheath layer 4. Conductor layer 1: It is formed by multiple strands of tin-plated copper wires through five types of stranding structure, wherein the diameter of a single wire is 0.22mm, the outer diameter tolerance of the conductor is within ±0.02mm, and the surface of the copper wire has a gradient plating structure, including a nickel layer of 0.5μm, a silver layer of 1.5μm and an organosilicon protective layer of 0.1μm from the inside out; Semiconductor resistive water layer 2: The conductor layer is wrapped with a 20% overlap rate using a longitudinal wrapping process; Cross-linked polyethylene insulation layer 3: an inner shielding layer, an insulation layer, and an outer shielding layer formed simultaneously through a three-layer co-extrusion process, with an extrusion temperature of 165℃ and an extrusion pressure of 22MPa; The composite shielding structure layer includes: Copper wire braided shielding layer 5: formed by loosely braiding tin-plated copper wire with a diameter of 0.12mm at an 85% coverage rate and a braiding angle of 50°; Semiconductor resistive water tape 6: wrapped in a spiral manner on the outer surface of the copper wire braided shielding layer; Dense sheath layer 4: Made of low-smoke, halogen-free, flame-retardant polyolefin material, with a cross-sectional porosity of no more than 0.3% and a density of no less than 0.95 g / cm³. 3 Tensile strength not less than 18 MPa, comprising, by weight: 60 parts of ethylene-vinyl acetate copolymer; 12 parts of nano-sized silica; 15 parts of magnesium hydroxide flame retardant; 2.5 parts of silane coupling agent; Antioxidant 0.5 parts; Five parts of aminated multi-walled carbon nanotubes; The tin-plated copper wire of conductor layer 1 is annealed under nitrogen protection before stranding. The annealing temperature is 450℃ and the stranding speed is 14m / min. After annealing, the copper wire elongation is ≥35%, and a protective gas containing 0.5 vol% rare earth lanthanum is introduced during the annealing process. A ceramicized silicone rubber filler layer is provided between the copper wire braided shielding layer 5 and the semi-conductive resistive water tape 6. The oxygen index of the filler layer is not less than 35%, and it includes: 100 parts of methyl vinyl silicone rubber matrix; 50 parts of aluminum hydroxide flame retardant; 15 parts glass powder; 1.0 part of platinum catalyst; Five portions of shape memory polyurethane microspheres; The molding die for the dense sheath layer 4 has a tapered flow channel structure and is equipped with a rotary extrusion device with a rotation speed of 120 rpm. When conductor layer 1 adopts a five-type stranded structure, the number of copper wires in each strand is distributed in an arithmetic sequence with a tolerance of 6 wires. The number of copper wires in the outermost strand is 60, and the strand pitch ratio between adjacent strands changes in a 1:1.23 manner. Silicon grease lubricant containing nano-diamond particles is filled in the stranding gap. The substrate of the semiconducting resistive water layer 2 is a polyester fiber reinforced composite material, including: Low-density polyethylene 55wt% 8wt% carbon nanotube conductive filler; 20wt% water-absorbing and expanding resin particles; 10 wt% polyester staple fiber; Graphene quantum dots 1.2 wt%; The radial dielectric constant gradient distribution of the cross-linked polyethylene insulation layer 3 satisfies the following: dielectric constant ε1=2.30 for the inner shielding layer, ε2=2.28 for the insulation layer, and ε3=2.35 for the outer shielding layer. Furthermore, the insulation layer contains dispersed sheet-like boron nitride nanofillers with a mass fraction of 1.5% and a diameter-to-thickness ratio >150:1. The surface of the tin-plated copper wire of the copper wire braided shielding layer 5 is coated with a nano-silver / graphene composite coating with a thickness of 80nm, and titanium dioxide photocatalytic particles with a diameter of 50nm are embedded in the coating. The dense sheath layer 4 contains aminated multi-walled carbon nanotubes with a length distribution of 5 μm and an outer diameter of 12 nm. These nanotubes are chemically bonded to the matrix material through a polyethylene compatibilizer grafted with maleic anhydride. The processing steps for this copper core cross-linked polyethylene dense extruded sheathed power cable are as follows: S1. Conductor pretreatment: The tin-plated copper wire is annealed under nitrogen protection containing rare earth elements at a temperature of 450°C. After cooling to 80°C, it is stranded at a speed of 14 m / min, and nano-diamond lubricant is sprayed simultaneously during the stranding process. S2. Insulation layer processing: Longitudinal wrapping of semi-conductive resistive water layer 2 and preheating to 110℃ for roll forming; The three-layer co-extrusion process is carried out through a CCV overhead cross-linking production line with an extrusion temperature of 165℃ and a vulcanizing tube temperature divided into three zones. Zone 1: 175℃; Zone 2: 215℃; Zone 3: 225℃. S3, Composite Shielding Processing: Braided copper wire shielding layer 5, coverage 85%, braiding angle 50°; Spiral-wound semiconducting resistive water tape 6, wrapping tension 5N; S4, Irradiation crosslinking: Basic irradiation of 12Mrad using an electron accelerator; S5, Steam secondary crosslinking: 0.8MPa saturated steam treatment for 6h, with 5kHz ultrasonic oscillation applied during the treatment; S6. Sheath Forming: The sheath is processed using a two-stage extruder with a die pressure of 30MPa and a screw length-to-diameter ratio of 32:1. After extrusion, it is immediately subjected to liquid nitrogen quenching treatment with a cooling rate of ≥50℃ / s.
[0022] Example 4: Please refer to Figure 1 An embodiment of the present invention provides a copper core cross-linked polyethylene dense extruded sheathed power cable, which, from the inside out, comprises: a conductor layer 1, a semi-conductive water-resistant layer 2, a cross-linked polyethylene insulation layer 3, a composite shielding structure layer, and a dense sheath layer 4. Conductor layer 1: It is formed by multiple strands of tin-plated copper wires through five types of stranding structure, wherein the diameter of a single wire is 0.21mm, the outer diameter tolerance of the conductor is within ±0.02mm, and the surface of the copper wire has a gradient plating structure, including a nickel layer of 0.6μm, a silver layer of 1.3μm and an organosilicon protective layer of 0.18μm from the inside out; Semiconductor resistive water layer 2: The conductor layer is wrapped with a longitudinal wrapping process with an overlap rate of 18%; Cross-linked polyethylene insulation layer 3: an inner shielding layer, an insulation layer, and an outer shielding layer formed simultaneously through a three-layer co-extrusion process, with an extrusion temperature of 162℃ and an extrusion pressure of 21MPa; The composite shielding structure layer includes: Copper wire braided shielding layer 5: formed by loosely braiding tin-plated copper wire with a diameter of 0.12mm at an 88% coverage rate and a braiding angle of 48°; Semiconductor resistive water tape 6: wrapped in a spiral manner on the outer surface of the copper wire braided shielding layer; Dense sheath layer 4: Made of low-smoke, halogen-free, flame-retardant polyolefin material, with a cross-sectional porosity of no more than 0.3% and a density of no less than 0.95 g / cm³. 3 Tensile strength not less than 18 MPa, comprising, by weight: 71 parts of ethylene-vinyl acetate copolymer; 9 parts of nano-sized silica; 16 parts of magnesium hydroxide flame retardant; 2.2 parts of silane coupling agent; Antioxidant 1.1 parts; Five parts of aminated multi-walled carbon nanotubes; The tin-plated copper wire of conductor layer 1 is annealed under nitrogen protection before stranding. The annealing temperature is 470℃ and the stranding speed is 13m / min. After annealing, the copper wire elongation is ≥35%, and a protective gas containing 0.9 vol% rare earth lanthanum is introduced during the annealing process. A ceramicized silicone rubber filler layer is provided between the copper wire braided shielding layer 5 and the semi-conductive resistive water tape 6. The oxygen index of the filler layer is not less than 35%, and it includes: 100 parts of methyl vinyl silicone rubber matrix; 48 parts of aluminum hydroxide flame retardant; 16 parts glass powder; 0.5 parts platinum catalyst; Six portions of shape memory polyurethane microspheres; The molding die for the dense sheath layer 4 has a tapered flow channel structure and is equipped with a rotary extrusion device with a rotation speed of 98 rpm. When conductor layer 1 adopts a five-type stranded structure, the number of copper wires in each stranded layer is distributed in an arithmetic sequence with a tolerance of 7 wires. The number of copper wires in the outermost stranded layer is 52, and the strand pitch ratio between adjacent stranded layers changes in a 1:1.30 increment. The stranding gap is filled with silicone grease lubricant containing nanodiamond particles. The substrate of the semiconducting resistive water layer 2 is a polyester fiber reinforced composite material, including: 48 wt% low-density polyethylene; 9wt% carbon nanotube conductive filler; 20wt% water-absorbing and expanding resin particles; 11 wt% polyester staple fiber; Graphene quantum dots 1.2 wt%; The radial dielectric constant gradient distribution of the cross-linked polyethylene insulation layer 3 satisfies the following: dielectric constant ε1=2.36 for the inner shielding layer, ε2=2.24 for the insulation layer, and ε3=2.42 for the outer shielding layer. Furthermore, the insulation layer contains dispersed sheet-like boron nitride nanofillers with a mass fraction of 0.9% and a diameter-to-thickness ratio >150:1. The surface of the tin-plated copper wire of the copper wire braided shielding layer 5 is coated with a nano-silver / graphene composite coating with a thickness of 88nm, and titanium dioxide photocatalytic particles with a diameter of 40nm are embedded in the coating. The dense sheath layer 4 contains aminated multi-walled carbon nanotubes with a length distribution of 9 μm and an outer diameter of 11 nm, which are chemically bonded to the matrix material through a polyethylene compatibilizer grafted with maleic anhydride. The processing steps for this copper core cross-linked polyethylene dense extruded sheathed power cable are as follows: S1. Conductor pretreatment: The tin-plated copper wire is annealed under nitrogen protection containing rare earth elements at a temperature of 460°C. After cooling to 80°C, it is stranded at a speed of 12 m / min, and nano-diamond lubricant is sprayed simultaneously during the stranding process. S2. Insulation layer processing: Longitudinal wrapping of semi-conductive resistive water layer 2 and preheating to 120℃ for roll forming; The three-layer co-extrusion process is carried out through a CCV overhead cross-linking production line with an extrusion temperature of 162℃ and a vulcanizing tube temperature divided into three zones. Zone 1: 181℃; Zone 2: 211℃; Zone 3: 229℃; S3, Composite shielding processing: Braided copper wire shielding layer 5, coverage 88%, braiding angle 48°; Spiral-wound semiconducting resistive water tape 6, wrapping tension 4N; S4, Irradiation crosslinking: Basic irradiation of 12Mrad using an electron accelerator; S5, Steam secondary crosslinking: 1MPa saturated steam treatment for 5h, with 6kHz ultrasonic oscillation applied during the treatment; S6. Sheath Forming: The sheath is processed using a two-stage extruder with a die pressure of 27MPa and a screw length-to-diameter ratio of 32:1. After extrusion, it is immediately subjected to liquid nitrogen quenching treatment with a cooling rate of ≥50℃ / s.
[0023] Comparative Example 1: A densely extruded sheathed power cable with a copper core and cross-linked polyethylene was prepared according to the method of Example 1. The difference from Example 1 is that aminated multi-walled carbon nanotubes were not added to the sheath layer, while the other raw materials, steps and parameters were the same as in Example 1.
[0024] Comparative Example 2: A densely extruded sheathed power cable with a copper core and cross-linked polyethylene was prepared according to the method of Example 1. The difference from Example 1 is that the conductor stranding was not filled with nano-diamond lubricant, but with ordinary silicone grease lubricant. Other raw materials, steps and parameters were the same as in Example 1.
[0025] Comparative Example 3: A densely extruded sheathed power cable with a copper core and cross-linked polyethylene was prepared according to the method of Example 1. The difference from Example 1 is that the dielectric constant gradient design of the insulation layer was cancelled, and the three-layer co-extrusion adopted homogeneous cross-linked polyethylene with ε=2.30. Other raw materials, steps and parameters were the same as in Example 1.
[0026] Comparative Example 4: A densely extruded sheathed power cable with a copper core and cross-linked polyethylene was prepared according to the method of Example 1. The difference from Example 1 is that ultrasonic oscillation was eliminated during the secondary cross-linking process with steam, while the other raw materials, steps and parameters were the same as in Example 1.
[0027] Comparative Example 5: A densely extruded sheathed power cable with a copper core and cross-linked polyethylene, prepared according to the method of Example 1, except that rare earth lanthanum element in the conductor annealing process is not added, while other raw materials, steps and parameters are the same as in Example 1.
[0028] Comparative Example 6: A densely extruded sheathed power cable with a copper core and cross-linked polyethylene was prepared according to the method of Example 1. The difference from Example 1 is that the ceramicized silicone rubber filling layer between the copper wire braided shielding layer and the water-blocking tape was removed. Other raw materials, steps and parameters were the same as in Example 1.
[0029] Comparative Example 7: A densely extruded sheathed power cable with a copper core and cross-linked polyethylene was prepared according to the method of Example 1. The difference from Example 1 is that the nano-silver / graphene composite coating on the copper wire of the shielding layer was removed, and only the basic tin plating layer was retained. Other raw materials, steps and parameters were the same as in Example 1.
[0030] Performance testing: Test 1: Conductor DC resistance test: Cut a 1.000±0.001m sample from the copper core cross-linked polyethylene dense extruded sheathed power cable obtained in Examples 1-4 and Comparative Examples 1-7, strip the insulation from both ends to expose 30mm of conductor, wipe the conductor surface with alcohol to remove the oxide layer, and place it in a DC resistance tester for testing.
[0031] Test 2: Partial discharge quantity test: Cut 10m lengths of the copper core cross-linked polyethylene dense extruded sheathed power cables obtained in Examples 1-4 and Comparative Examples 1-7, strip the sheaths at both ends to expose the insulation layer, ground the conductors, and use a partial discharge detector to record the maximum discharge quantity under stable conditions.
[0032] Test 3: Sheath tensile strength test: 2mm thick sheets of copper core cross-linked polyethylene dense extruded sheathed power cables obtained in Examples 1-4 and Comparative Examples 1-7 were cut from the sheath layer and placed in an electronic tensile testing machine for testing.
[0033] Test 4: Shielding transfer impedance test: Take a 3m sample of the copper core cross-linked polyethylene dense extruded sheathed power cable obtained in Examples 1-4 and Comparative Examples 1-7, pass it through the inner conductor, weld SMA connectors at both ends, attach the outer shielding clamp shell, and place it in the shielding transfer impedance tester for testing.
[0034] Test 5: Oxygen Index Test: The copper core cross-linked polyethylene dense extruded sheathed power cables obtained in Examples 1-4 and Comparative Examples 1-7 were used to prepare 80×10×3mm samples. Starting from an oxygen concentration of 30%, the samples were adjusted in 0.2% increments, and the minimum oxygen concentration required for burning for 3 minutes or 50mm of length was recorded.
[0035] Test 6: Stranding tightness test: The copper core cross-linked polyethylene dense extruded sheathed power cables obtained in Examples 1-4 and Comparative Examples 1-7 were tested by measuring the actual outer diameter (d1) and theoretical outer diameter (d0) of the stranded conductors using a laser diameter gauge, and the stranding tightness (f) was calculated using a formula.
[0036] Table 1. Performance Test Data Table
[0037]
[0038] Furthermore, through the synergistic effect of rare earth element-assisted annealing (0.5–1.0 vol% lanthanum) and nanodiamond lubricant filling, the conductor elongation was ≥35%, the stranding tightness was ≥98.4%, and the DC resistance was reduced to 0.124–0.126 Ω / km. Compared with the control group without this process, the resistance was reduced by 5.6%–10.4%, which verified the repair effect of rare earth elements on copper grain boundary defects and the effect of nano lubricant on improving stranding tightness. By setting a radial dielectric constant gradient distribution of inner shielding layer ε1=2.30~2.40, insulation layer ε2=2.22~2.28, and outer shielding layer ε3=2.35~2.45, and combining it with sheet-like boron nitride filler (0.8~1.5 wt%) with a diameter-to-thickness ratio >150:1, the partial discharge quantity was stabilized at 8.1~8.3 pC. This value is only 28.2% of that of the homogeneous insulation structure (Comparative Example 3, 28.7 pC), which confirms that gradient design can significantly optimize the electric field distribution. The introduction of a ceramicized silicone rubber filler layer (oxygen index ≥35%) reduces the shielding transfer impedance to ≤18.4 mΩ / m, while the impedance rises to 42.6 mΩ / m (Comparative Example 6) when this layer is absent, representing a decrease of 56.8%. The nano-silver / graphene composite coating (containing 20–50 nm TiO2 photocatalytic particles) reduces the contact impedance of the shielding layer by 70.4% (compared to 31.2 mΩ / m in Comparative Example 7), and the two work together to ensure the continuity of electromagnetic shielding. Aminated multi-walled carbon nanotubes are chemically bonded through maleic anhydride grafting, resulting in a sheath tensile strength ≥22.4 MPa and an oxygen index ≥36.2%. Without maleic anhydride (Comparative Example 1), the strength decreases by 19.5% and the flame retardancy decreases by 10.1%. Ultrasonic-assisted steam crosslinking combined with liquid nitrogen quenching (≥50℃ / s) significantly improved the crosslinking density, resulting in a 14.6% increase in strength compared to the process without ultrasound (Comparative Example 4). Furthermore, key performance characteristics are simultaneously improved through gradient insulation design, application of nano-reinforced materials (carbon nanotubes / boron nitride / diamond), composite shielding structures, and multi-energy field synergistic processes (rare earth annealing / ultrasonic crosslinking / rotary extrusion). By using rare earth element annealing and nano-diamond lubricant filling, the DC resistance of the conductor is significantly reduced, while achieving ultra-high stranding tightness, effectively improving current carrying efficiency and mechanical stability. Through the synergistic effect of radial dielectric constant gradient design and lamellar boron nitride filler, the partial discharge is reduced to an extremely low level, which is far superior to homogeneous insulation structure and significantly enhances the reliability of high voltage insulation. The cascade shielding mechanism of ceramicized silicone rubber filler layer and nano silver / graphene composite coating significantly reduces transfer impedance and meets the stringent high-frequency interference shielding requirements. By combining the chemical bonding enhancement of aminated carbon nanotubes with the rotary extrusion process, the sheath possesses high tensile strength, low porosity, and excellent flame retardancy, far exceeding the performance of conventional sheaths. The crosslinking density and crystallization quality of the material are significantly improved by ultrasonic-assisted crosslinking and liquid nitrogen quenching processes. Combined with integrated molding control, the structural accuracy and performance consistency are guaranteed.
[0039] Working principle: Through the synergistic design of gradient-plated conductors and Category 5 stranding technology, conductivity and structural stability are significantly improved. Combined with an insulation layer with a gradient dielectric constant and a composite shielding structure, breakthrough suppression of partial discharge and optimization of electromagnetic shielding effectiveness are achieved. Supplemented by a nano-reinforced sheath and ultrasonic cross-linking and liquid nitrogen quenching manufacturing processes, the cable simultaneously possesses ultra-high mechanical strength, extremely low porosity, and excellent flame-retardant properties. Its overall performance far exceeds that of conventional power cables. Rare earth element annealing treatment and nano-diamond lubricant filling significantly reduce conductor DC resistance while achieving ultra-high stranding tightness, effectively improving current-carrying efficiency and mechanical stability. Through radial dielectric constant... The synergistic effect of gradient design and sheet-like boron nitride filler reduces partial discharge to an extremely low level, far superior to homogeneous insulation structures, significantly enhancing high-voltage insulation reliability. The cascade shielding mechanism of ceramicized silicone rubber filler layer and nano-silver / graphene composite coating greatly reduces transfer impedance, meeting stringent high-frequency interference shielding requirements. The synergistic effect of aminated carbon nanotube chemical bonding enhancement and rotary extrusion process enables the sheath to simultaneously possess high tensile strength, low porosity, and excellent flame retardancy, far exceeding the performance of conventional sheaths. Ultrasonic-assisted crosslinking and liquid nitrogen quenching processes significantly improve the crosslinking density and crystal quality of the material. Combined with integrated molding control, structural precision and performance consistency are guaranteed.
[0040] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
Claims
1. A densely extruded sheathed power cable with a copper core and cross-linked polyethylene, characterized in that: From the inside out, it includes: conductor layer (1), semiconducting resistive water layer (2), cross-linked polyethylene insulation layer (3), composite shielding structure layer and dense sheath layer (4). Conductor layer (1): formed by multiple strands of tin-plated copper wires through five types of stranding structure, wherein the diameter of a single wire is 0.18mm to 0.22mm, the outer diameter tolerance of the conductor is within ±0.02mm, and the surface of the copper wire has a nickel layer of 0.5 to 0.8μm, a silver layer of 1.2 to 1.5μm and an organosilicon protective layer of 0.1 to 0.2μm arranged sequentially from the inside to the outside, wherein the nickel layer and the silver layer are plating layers, and the organosilicon protective layer is a coating protective layer; Semiconductor resistive water layer (2): The conductor layer is covered by a longitudinal wrapping process with an overlap rate of 15% to 20%; Cross-linked polyethylene insulation layer (3): an inner shielding layer, an insulation layer and an outer shielding layer are formed simultaneously by a three-layer co-extrusion process. The extrusion temperature is 150℃~165℃ and the extrusion pressure is 18MPa~22MPa. The radial dielectric constant of the cross-linked polyethylene insulation layer (3) satisfies the following: dielectric constant of the inner shielding layer ε1=2.35±0.05, dielectric constant of the insulation layer ε2=2.25±0.03, dielectric constant of the outer shielding layer ε3=2.40±0.05, and ε1 and ε3 are both greater than ε2. The composite shielding structure layer includes a copper wire braided shielding layer (5) and a semi-conductive resistive water strip (6). Copper wire braided shielding layer (5): formed by loosely braiding tin-plated copper wire with a diameter of 0.12mm at a coverage rate of 85% to 90% and a braiding angle of 45° ± 5°; Semiconducting resistive water tape (6): wrapped around the outer surface of the copper wire braided shielding layer (5) in a spiral wrapping manner; Dense sheath layer (4): Made of low-smoke halogen-free flame-retardant polyolefin material, with a cross-sectional porosity of not more than 0.3% and a density of not less than 0.95 g / cm³. 3 Tensile strength not less than 18 MPa, comprising, by weight: 60-75 parts of ethylene-vinyl acetate copolymer; 8-12 parts of nano-sized silica; 15-20 parts of magnesium hydroxide flame retardant; 1.5–2.5 parts of silane coupling agent; Antioxidant 0.5–1.2 parts; 3-5 parts of aminated multi-walled carbon nanotubes.
2. The copper core cross-linked polyethylene dense extruded sheathed power cable according to claim 1, characterized in that: The tin-plated copper wire of the conductor layer (1) is annealed under nitrogen protection before stranding. The annealing temperature is 450℃~480℃ and the stranding speed is 12m / min~14m / min. After annealing, the copper wire elongation is ≥35%. During the annealing process, a protective gas containing rare earth lanthanum is introduced. The volume content of rare earth lanthanum in the protective gas is 0.5~1.0% based on lanthanum.
3. The copper core cross-linked polyethylene dense extruded sheathed power cable according to claim 1, characterized in that: A ceramicized silicone rubber filler layer is provided between the copper wire braided shielding layer (5) and the semiconducting resistive water tape (6), the oxygen index of the filler layer being not less than 35%, comprising: 100 parts of methyl vinyl silicone rubber matrix; 40-50 parts of aluminum hydroxide flame retardant; 15-20 parts glass powder; Platinum catalyst 0.5–1.0 parts; 5-8 parts of shape memory polyurethane microspheres.
4. The copper core cross-linked polyethylene dense extruded sheathed power cable according to claim 1, characterized in that: The molding die of the dense sheath layer (4) has a conical flow channel structure and is equipped with a rotary extrusion device with a rotation speed of 80 rpm to 120 rpm.
5. The copper core cross-linked polyethylene dense extruded sheathed power cable according to claim 1, characterized in that: When the conductor layer (1) adopts a five-type stranded structure, the number of copper wires in each strand is distributed in an arithmetic sequence with a tolerance of 6 to 8 wires. The number of copper wires in the outermost strand is 50 to 60, and the strand pitch ratio of adjacent strands changes from 1:1.28±0.
05. Silicon grease lubricant containing nano-diamond particles is filled in the stranding gap.
6. The copper core cross-linked polyethylene dense extruded sheathed power cable according to claim 1, characterized in that: The substrate of the semiconducting resistive water layer (2) is a polyester fiber reinforced composite material, comprising: Low-density polyethylene 45-55 wt% Carbon nanotube conductive filler 8–12 wt%; Water-absorbing and expanding resin particles 15-20 wt%; Polyester staple fiber 10-15 wt%; Graphene quantum dots: 0.5–1.2 wt%.
7. The copper core cross-linked polyethylene dense extruded sheathed power cable according to claim 1, characterized in that: The cross-linked polyethylene insulation layer (3) contains sheet-like boron nitride nanofillers with a mass fraction of 0.8% to 1.5% and a diameter-to-thickness ratio of >150:
1.
8. The copper core cross-linked polyethylene dense extruded sheathed power cable according to claim 1, characterized in that: The tin-plated copper wire of the copper wire braided shielding layer (5) is coated with a nano-silver / graphene composite coating with a thickness of 80-120nm, and titanium dioxide photocatalytic particles with a diameter of 20-50nm are embedded in the coating.
9. The copper core cross-linked polyethylene dense extruded sheathed power cable according to claim 1, characterized in that: The aminated multi-walled carbon nanotubes in the dense sheath layer (4) have a length distribution of 5-15 μm and an outer diameter of 8-12 nm, and are chemically bonded to the matrix material through a polyethylene compatibilizer grafted with maleic anhydride.
10. The processing technology of the copper core cross-linked polyethylene dense extruded sheathed power cable according to any one of claims 1-9, characterized in that, The processing steps for this copper core cross-linked polyethylene dense extruded sheathed power cable are as follows: S1. Conductor pretreatment: The tin-plated copper wire is annealed under nitrogen protection containing rare earth lanthanum. The volume content of rare earth lanthanum in the protective gas is 0.5-1.0% based on lanthanum. The annealing temperature is 450℃-480℃. After cooling to 80℃, it is stranded at 12m / min-14m / min. During the stranding process, nano-diamond lubricant is sprayed simultaneously. S2, Insulation layer processing: Longitudinal wrapping of semi-conductive resistive water layer (2) and preheating to 110℃~120℃ for roll forming; The three-layer co-extrusion process is carried out through a CCV overhead cross-linking production line with an extrusion temperature of 150℃~165℃ and a vulcanizing tube temperature divided into three zones. Zone 1: 180℃±5℃; Zone 2: 210℃±5℃; Zone 3: 230℃±5℃. S3, Composite shielding processing: Braided copper wire shielding layer (5), coverage rate 85%~90%, braiding angle 45°±5°; Spiral-wound semiconducting resistive water tape (6), with a wrapping tension of 3N to 5N; S4, Irradiation crosslinking: Basic irradiation of 12Mrad to 15Mrad using an electron accelerator; S5. Secondary crosslinking with steam: 0.8MPa~1.2MPa saturated steam treatment for 4h~6h, with ultrasonic oscillation of 5~8kHz applied during the treatment; S6. Sheath Forming: The sheath is processed using a two-stage extruder with a die pressure of 25MPa~30MPa and a screw length-to-diameter ratio of 32:
1. After extrusion, it is immediately subjected to liquid nitrogen quenching treatment with a cooling rate ≥50℃ / s.
Citation Information
Patent Citations
Cross-linked polyethylene insulated double-sheath power cable
CN101814335A
Electric power cable
US20100186988A1
Electric power cable
US20170330649A1
Electric power cable
US5006670A
Charring-boosting low-smoke zero-halogen nanometer flame-retardant composite material of ethylene-vinyl acetate copolymer and preparation method thereof
CN106496759A
